Synthesis of Polymeric Chelating Ligands from Sago Starch for Metal Removal from Electroplating Wastewater - Lutfor, M. R.; M. M., Yusoff; Muhammad Nor Fazli, Abd Malek (Council of Scientific and Industrial Research, 2014)
Polymeric chelating ligands containing hydroxamic acid and amidoxime ligands were synthesized from poly(methyl acrylate-co-acrylonitrile) grafted sago starch. Batch adsorption was performed to identify the binding property of metal ions. Maximum sorption capacity of copper is 2.80 mmol g-1, however, other transition metals has good sorption capacity with this legends. The rate of exchange of some metals was fast, i.e. t½  6 minutes (average). Three types of wastewater containing chromium, zinc, nickel, copper, and iron were used in this study. The metal recovery is found to be high, and more than 99% of the metals could be removed from the metal plating wastewater. Polymeric chelating ligands could be used to remove the metals from wastewater.